DIVERSITY OF BEGOMOVIRUS AND INSECT VECTORS BEMISIA TABACI THROUGH A GENOMIC APPROACH FOR THE MOLECULAR SURVEILLANCE SYSTEM OF YELLOWING DISEASES IN VEGETABLE CROPS - Meliansyah, Rika
Yellowing diseases in vegetable plants are caused by Begomovirus with the insect vector Bemisia tabaci which can reduce the quality and quantity of crop yields. Typical symptoms of the disease in the form of yellow leaves are found in many vegetable crops with an incidence rate of up to 100%. Control of yellowing diseases in vegetable crops is still a challenge, especially in understanding the pathosystem of yellowing diseases as a basis for developing control strategies. This study aimed to survey cases of yellowing diseases in the vegetable centres of Java and Sumatra, to characterize the diversity of Begomovirus present in B. tabaci vector insects using a genomic approach, to confirm the dominant Begomovirus species using specific primers, and to identify the diversity of B. tabaci at the survey site. The research method includes a survey of symptom variations and disease incidence rates with parameters of observing land conditions, symptom descriptions and disease incidence calculations. Characterization of the Begomovirus genus from insect vectors was carried out using Illumina® Mate Pair Sequencing, B. tabaci diversity analysis using mtCOI (mitochondrial cytochrome oxidase subunit I gene) markers and Begomovirus identification in B. tabaci by amplification of the coat protein gene using specific primers. The results showed that in 57 vegetable growing areas consisting of 21 chilli growing fields, 11 tomato growing fields and 25 eggplant growing fields were observed in West Java (Bandung, Garut, Tasikmalaya Regencies; Central Java (Semarang, Temanggung, Wonosobo, Magelang); East Java (Jombang, Kediri, Batu City, Malang, Lumajang, Probolinggo); West Sumatra (Padang Panjang City, Agam, Tanah Datar); Jambi (Muaro Jambi, Bungo, Merangin); North Sumatra (Deli Serdang, South Binjai, Karo, Pematang Siantar, Simalungun), there are variations in the symptoms of yellowing diseases. The symptoms found include blanching of the veins and thickening of the veins, mosaic, leaf edges curling upwards, leaf malformations, yellow and curly leaves, small bright yellow leaves and stunted plants. The characteristic symptom of yellowing diseases in chillies and eggplants is bright yellow leaves, tomato plants are mild mosaic leaves with leaf edges curling upwards. Characteristic observations of symptoms in vegetable growing beds show that yellowing symptoms in chillies and eggplants are visible compared to symptoms in tomato plants. This will facilitate the implementation of conventional disease monitoring. The incidence rate of yellowing diseases in Java and Sumatra on chilli, tomato and eggplant varies between 5-100%. A 100% incidence of the disease is generally indicated by smaller and yellow leaves on chilli or eggplant in vegetable-growing fields. Information on the typical symptoms of yellowing diseases due to Begomovirus can support the implementation of plant disease management as early detection in eliminating the causes of plant diseases. Begomovirus diversity through Next Generation Sequencing (NGS) genomic approach with Illumina® Mate Pair Sequencing technology and using de novo bioinformatics analysis managed to detect 2 contigs DNA A and DNA B Tomato yellow leaf curl Kanchanabury virus (TYLCKaV), 28 contigs Biotype B B.tabaci namely Meam 1 (Biotype B), 376 other contigs were other viruses, Unidentified Cotton leaf curl Rajasthan virus-associated DNA clone pNDM1.5 partial sequence. Bioinformatics analysis using a reference-based assembly approach yielded 2 contigs TYLKaV (DNA A and B) and Pepper yellow leaf curl Indonesia virus (PYLCIV). An approach based on this research can become the basis for a molecular monitoring system for plant diseases, especially those transmitted by insect vectors. This is because NGS can detect Begomovirus species and B. tabaci biotypes which are suspected to be dominant and can detect new species that require further research. Confirmation and validation of NGS results using B. tabaci genetic diversity analysis with the target mtCOI mitochondrial gene which was reconstructed by constructing a Neighbor-Joining phylogenetic tree yielded 32 sequences which all belonged to the Non B Biotype klade, the results of the analysis were different from the NGS results, namely Biotype Meam 1, but Thus, in the Non B klade, there is 1 MEAM 1 biotype from Indonesia and 1 Asian Biotype from Korea. This can be used to support the results of this study. Identification of Begomovirus on B. tabaci with specific primers was successful in detecting TYLCKaV and PYLCV as viruses that are commonly found in Java and Sumatra, and TYLCKaV as the dominant Begomovirus. In this study, the genomic approach is not only a detection method for identification and diversity but provides implications for molecular surveillance systems that can support yellowing disease control strategies.